Small molecule displacement of a cryptic degron causes conditional protein degradation - Bonger, Kimberly M. (2011)
The ability to rapidly regulate the functions of specific proteins in living cells is a valuable tool for biological research. Here we describe a novel technique by which the degradation of a specific protein is induced by a small molecule. A protein of interest is fused to a Ligand-Induced Degradation (LID) domain resulting in the expression of a stable and functional fusion protein. The LID domain is comprised of the FK506- and rapamycin-binding protein (FKBP) and a 19-amino acid degron fused to the C-terminus of FKBP. In the absence of the small molecule Shield-1, the degron binds to the FKBP protein and the fusion protein is stable. Shield-1 binds tightly to FKBP thereby displacing the degron and inducing rapid and processive degradation of the LID domain and any fused partner protein. Structure-function studies of the 19-residue peptide showed that a four-amino acid sequence within the peptide is responsible for degradation.